2008
DOI: 10.2975/31.4.2008.280.290
|View full text |Cite
|
Sign up to set email alerts
|

An update on randomized controlled trials of evidence-based supported employment.

Abstract: The current review is consistent with earlier reviews, although the evidence for high-fidelity IPS appears to be somewhat stronger here than in reviews evaluating studies with more heterogeneity in the supported employment models examined. The number, consistency, and effect sizes of studies of evidence-based supported employment establish it as one of the most robust interventions available for persons with severe mental illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
478
3
22

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 607 publications
(520 citation statements)
references
References 54 publications
17
478
3
22
Order By: Relevance
“…Although there are evidence-based studies on barriers to and facilitators of employment of persons with a mental disability in HICs [5,12,14], few studies have systematically explored the subject in African countries [15]. This, combined with calls in the United Nations Convention on the Rights of Persons with Disabilities (UNCRPD) [16] and the Sustainable Development Goals (SDGs) [17], have advocated concerted action to protect the rights of persons with disabilities and their empowerment through inclusion in socioeconomic programmes.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are evidence-based studies on barriers to and facilitators of employment of persons with a mental disability in HICs [5,12,14], few studies have systematically explored the subject in African countries [15]. This, combined with calls in the United Nations Convention on the Rights of Persons with Disabilities (UNCRPD) [16] and the Sustainable Development Goals (SDGs) [17], have advocated concerted action to protect the rights of persons with disabilities and their empowerment through inclusion in socioeconomic programmes.…”
Section: Introductionmentioning
confidence: 99%
“…Continual support should, when required, be provided to increase the employee's chances of retaining employment. This method has proven to be successful in obtaining jobs for people with disabilities, not only in Sweden (Germundsson et al 2012) but also in other countries (Burns et al 2007;Bond, Drake & Becker 2008). Although successful, the method is limited to providing change in labour market status on the individual level; barriers to employment remain for 1.…”
Section: Supported Employmentmentioning
confidence: 99%
“…Clinical trials have shown IPS to be associated with higher CE rates, shorter time to entering CE, greater numbers of hours worked per week, and more weeks worked per year among individuals diagnosed with SMI [13,[16][17][18][19][20][21][22][23][24][25][26] and, most recently, among veterans with posttraumatic stress disorder (PTSD) [27]. The program is most effective when fidelity to the model is high [28][29][30].…”
Section: Supported Employmentmentioning
confidence: 99%